Pengaruh Pendidikan Terhadap Tingkat Kesehatan Masyarakat Kecamatan Suragala Kabupaten Lombok Timur Menggunakan Algoritma Random Forest - ., yahya; Nurhidayati; L. M. Samsu (Infotek: Jurnal Informatika dan Teknologi, 2024)
SDGs are a global concern of the international community, including the Indonesian nation. There are many activities carried out by the international community to address this SDGs issue. Starting from real actions in the field to a continuous data collection process. In Indonesia, data collection has been carried out repeatedly, but the follow-up to each data collection is felt to be lacking, therefore Hamzanwadi University, using the Gemilang Village Thematic KKN application, has also played an active role in the data collection process. However, up to now, information about data collection results and follow-up actions has not been provided properly, in fact none of the data collection results have been processed to obtain clear and measurable information. Through internal higher education research carried out by Hamzanwadi University, an attempt was made to carry out research starting with the SDGs data processing process, namely education and health, to provide knowledge and information about whether or not there is an influence of education on the health of the people of Suralaga District, East Lombok Regency, so that if the influence If education plays a significant role, the Suralaga District Government can take concrete steps to improve it in the future. From the results of data processing it can be concluded that the influence of education on the level of public health is very high, using 90% training data and 10% testing data can achieve an accuracy of 88.61%, which means 700 data show a positive trend of education on the level of public health